Microstructure and texture development during solid consolidation recycling of Ti-6Al-4V - Qi; Yau Tse; Rebecca Higginson (2018)
Ti-6Al-4V machining chips were recycled using equal channel angular pressing (ECAP). The microstructural and texture evolution of the recycled Ti-6Al-4V have been investigated using scanning electron microscopy, electron backscattered diffraction and transmission electron microscopy. For samples consolidated at 500 °C with a back-pressure of 100 MPa, the as-pressed density reached up to 99.9% after 8 passes. Pronounced grain refinement was also observed with increasing number of passes. The morphology of the grains has been changed from elongated and coarse to equiaxed and ultrafine as the number of passes increases. Strong textures were also introduced during multiple passes via Bc route. Texture has been developed with basal planes parallel to the inclination direction which is at 21° of the extrusion direction. After 4 and 8 passes, basal planes were rotated towards the transverse direction. No oxide can be detected at the chip-chip boundaries when the Ti-Al-4 V machining chips was consolidated at 500 °C. When the sample was processed at 550 °C, significant grain growth and clear oxide layers at the chip-chip interface were observed. In addition, the c-axis were rotated towards the longitudinal direction due to the non-basal slip activity. TEM observation revealed the dislocations presence in the 550 °C ECAP-processed sample.